0860 Sleep Disorders In Female Military Personnel. (27th May 2020) - Villarreal, B; Foster, S; Hansen, S; Brock, M; Sanchez, H; Gerwell, K; Carrizales, F; Peterson, A; Pruiksma, K; Mysliwiec, V
Abstract: Introduction: Sleep is an essential biological function and the disruption of sleep has deleterious consequences. Military personnel experience unique stressors related to their service, elevating the risk of developing sleep disorders. The etiologies and impact of sleep disorders on military women's health is poorly understood. This study is the first to prospectively assess whether military women with insomnia, obstructive sleep apnea (OSA), or comorbid insomnia and OSA (COMISA) have different gender roles, military service-associated factors, and biological characteristics than military men with the same disorders. Methods: This is a prospective observational study of military personnel with sleep disturbances. The study will evaluate women and men matched for sleep disorder. Participants will complete an evaluation to include polysomnography (PSG), sleep questionnaires and validated clinical assessments of associated disorders of interest. The baseline demographics, questionnaire, and PSG results will be analyzed to assess for commonalities or differences between genders. Results: We have enrolled 45 patients (24% female). Males had a higher BMI (29.1) than females (26). Males were also older (38) than females (35). The leading diagnosis in males was OSA (44%) and insomnia in females (64%). In males, the apnea-hypopnea index (AHI) was 11.3/hr, arousal index (ARI) was 20/hr, and sleep efficiency (SE) was 86.5%. Total sleep time (TST), wake after sleep onset (WASO), and sleep onset latency (SOL) were 364.6, 40.9, and 12.6 minutes, respectively. In females, the average AHI was 6.6/hr, ARI was 15/hr, and SE was 87.2%. Their TST, WASO, and SOL were 359, 44, and 12.6 minutes, respectively. Conclusion: Military personnel are at increased risk of sleep disorders. Literature comparing male and female characteristics and sleep disorders is scarce. In this study, baseline demographics were similar in both groups but insomnia was the leading diagnosis for women. This emphasizes the importance of adequate recognition and treatment of insomnia in this group. Support: This study is supported by the Defense Health Agency, Defense Medical Research and Development Program, Clinical Research Intramural Initiative for Military Women's Health.